Efek Penambahan Acetone pada Produk Pertalite untuk Menaikkan RON - Marsha Fazira Firdausy; Oktavia Salsa Winanda Pangestu; Rafli Ranu Rahmadian; Ikhsan Maulana; Oksil Venriza (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study was conducted with the primary goal of enhancing the octane number in Pertalite, a commonly used type of gasoline, through the addition of acetone as an additive. To achieve this objective, an experimental method involving the addition of various concentrations of acetone to Pertalite and measuring the resultant octane number using the Inductively Coupled Plasma (ICP) method was employed. Acetone, an organic compound from the ketone group, is known for its potential to increase the octane number in gasoline, which can subsequently affect engine performance and exhaust emissions. During the research, different concentrations of acetone were mixed into the fuel samples and their effectiveness in raising the octane number was measured. The results indicated a significant increase in the octane number of Pertalite with the addition of acetone. Further statistical analysis reinforced these findings, showing a significant correlation between increased acetone concentration and the enhancement of the octane number. This suggests that acetone can be considered an effective and economical additive for improving fuel quality. From these results, it can be concluded that acetone holds great potential as an economical additive that can significantly enhance fuel quality efficiently. These findings provide an important contribution to the fuel industry, particularly in the development of additives that can improve fuel performance while maintaining low production costs. It is hoped that these results will spur further research and practical applications in fuel formulation in the future.